Immunoglobulin E-mediated sensitization to pine and beech dust in relation to wood dust exposure levels and respiratory symptoms in the furniture industry - Vivi Schlünssen; Sabine Kespohl; Gitte Jacobsen; Monika Raulf-Heimsoth; Inger Schaumburg; Torben Sigsgaard (Nordic Association of Occupational Safety and Health (NOROSH), 2011)
OBJECTIVES: Wood dust exposure may cause Immunoglobulin E (IgE)-mediated allergic diseases. Our objectives were to estimate pine and beech dust sensitization rates among woodworkers and a reference group, explore the association between exposure and sensitization and between sensitization and respiratory symptoms, and finally investigate the impact of proteinogenic specific IgE (sIgE) epitopes on respiratory symptoms. METHODS: In a Danish study among 52 furniture factories and 2 reference factories, we evaluated the workers' asthma and rhinitis status using questionnaires and blood samples collected from 1506 woodworkers and 195 references. Workers with asthma symptoms (N=298), a random study sample (N=399) and a random rhinitis sample (N=100) were evaluated for IgE-mediated sensitization to pine and beech dust. RESULTS: The prevalence of pine and beech sensitization among current woodworkers was 1.7 and 3.1%, respectively. No differences in sensitization rates were found between woodworkers and references, but the prevalence of wood dust sensitization was dose-dependently associated with the current level of wood dust exposure. No relation was observed between wood dust sensitization per se and respiratory symptoms. Only symptomatic subjects had proteinogenic IgE epitopes to pine. Increased odds ratios for sIgE based on proteinogenic epitopes to beech and respiratory symptoms were found, although they were not statistically significant. CONCLUSIONS: Sensitization rates to pine and beech were the same for woodworkers and references but dependent on the current wood dust exposure level. The importance of beech and pine wood sensitization is limited, but may be of clinical significance for a few workers if the IgE epitopes are proteinogenic.